A versatile cryogenic system for liquid argon detectors. (1st March 2023) - Grauso, G.; Basco, A.; Canci, N.; de Asmundis, R.; Di Capua, F.; Matteucci, G.; Suvorov, Y.; Fiorillo, G.; ,
Abstract: Detectors for direct dark matter search using noble gases in the liquid phase as a detection medium need to be coupled to liquefaction, purification and recirculation systems. A dedicated cryogenic system has been assembled and operated at the INFN-Naples cryogenic laboratory with the aim to liquefy and purify the argon used as an active target in liquid argon detectors to study the scintillation and ionization signals detected by large SiPM arrays. The cryogenic system is mainly composed of a double wall cryostat hosting the detector, a purification stage to reduce the impurities below one part per billion level, a condenser to liquefy the argon, and a recirculation gas panel connected to the cryostat equipped with a custom gas pump. The main features of the cryogenic system are reported as well as the performance, long term operation and stability in terms of the most relevant thermodynamic parameters.